The effects of high-speed rail on accessibility and equity: Evidence from the Turin-Lyon case-study. (February 2023) - Bruzzone, Francesco; Cavallaro, Federico; Nocera, Silvio
Abstract: According to EU directives, cost-benefit analysis (CBA) is adopted to assess the impacts of high-speed rail (HSR). CBA evaluates the effectiveness of such infrastructure, determining whether and to what extent the present benefits overcome the present opportunity costs. However, it fails to include equity issues, which are the key aspects of transport planning. After a general discussion of equity in HSR and its link with the concept of accessibility, this study describes some complementary methods to calculate the variation in equity. Four of them (i.e. the potential accessibility index, spatial rail equity index, Gini index, and coefficient of variation) were adopted to assess the equity impacts for the Italian municipalities along the Turin-Lyon HSR. The results of the analysis reveal that despite a generalised increase in overall accessibility, equity implications are more contradictory, with main localities gaining further benefits compared to medium- and small-sized municipalities. In particular, the latter register a further increase in peripheralization . However, since they account for 36% of the total surface but represent only approximately 1% of the total population, the overall balance for the population served by the infrastructure may be considered positive. These results are particularly useful in contexts where the acceptance of HSR is weak, as they allow policymakers to identify adequate compensation measures to reduce the gap and increase territorial cohesion.